Exhibit and Marketing Techniques in Shopping Malls: The Example of Oakridge Centre - Mulongo, Absolom H. (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1988)
The architecture, organization and activities within a large shopping mall are described and analyzed. The mall is shown to both reflect and recreate the values of middle class Canadian culture. Both explicit and implicit comparisons are made with Zambian culture.